Investigation of Phenolic, Flavonoid and Total Antioxidant Capacity of Sumac (Rhus Coriaria L.) Plant Grown in Different Regions and Subjected to Different Preservation Methods - Ali, Haval; Çakmak, Meltem; Karatas, Fikret; Özer, Dursun; Saydam, Sinan (My University, 2024)
The total amount of phenolic and flavonoid compounds and the total antioxidant capacity of sumac samples grown in different regions were determined by spectrophotometer. Freshly ground samples were divided into three parts, first part analyzed immediately, second one oiled and third one kept as it is for six months. The total phenolic and flavonoid compounds were found in between 27.73-51.75 µg GAE (g dw)-1 and 16.16 -33.50 µg QE (g dw)-1, respectively for fresh samples. The samples that were grounded and kept for six months, the same parameters were observed to be 19.31 - 37.75 µg GAE (g dw)-1 and 10.76 -21.82 µg QE (g dw)-1, respectively. IC50 and TEAC values in freshly ground sumac samples were found between 14.79-23.80 µg mL-1 and 359.30-665.62 µmol trolox (g dw)-1, respectively. IC50 and TEAC values in the samples oiled were determined to be in between 17.51 - 27.70 µg mL-1 and 306.69 - 517.40 µmol trolox (g dw)-1, respectively. From these findings, it can be said that higher the amount of total phenolic and flavonoid compounds in the samples better the total antioxidant capacity. The decreases in the examined parameters of the samples with oil are lower than those kept without oiling (p>0.05). The differences in the examined parameters can be explained by the difference in geographical and ecological conditions.
Keywords: Phenolic substance; Preservation; Rhus coriaria L